Foreshock Properties at Typical and Enhanced Interplanetary Magnetic Field Strengths: Results From Hybrid‐Vlasov Simulations. Issue 7 (20th July 2018) - Turc, L.; Ganse, U.; Pfau‐Kempf, Y.; Hoilijoki, S.; Battarbee, M.; Juusola, L.; Jarvinen, R.; Brito, T.; Grandin, M.; Palmroth, M.
Abstract: In this paper, we present a detailed study of the effects of the interplanetary magnetic field (IMF) strength on the foreshock properties at small and large scales. Two simulation runs performed with the hybrid‐Vlasov code Vlasiator with identical setup but with different IMF strengths, namely, 5 and 10 nT, are compared. We find that the bow shock position and shape are roughly identical in both runs, due to the quasi‐radial IMF orientation, in agreement with previous magnetohydrodynamic simulations and theory. Foreshock waves develop in a broader region in the higher IMF strength run, which we attribute to the larger growth rate of the waves. The velocity of field‐aligned beams remains essentially the same, but their density is generally lower when the IMF strength increases, due to the lower Mach number. Also, we identify in the regular IMF strength run ridges of suprathermal ions which disappear at higher IMF strength. These structures may be a new signature of the foreshock compressional boundary. The foreshock wave field is structured over smaller scales in higher IMF conditions, due to both the period of the foreshock waves and the transverse extent of the wave fronts being smaller. While the foreshock is mostly permeated by monochromatic waves at typical IMF strength, we find that magnetosonic waves at different frequencies coexist in the other run. They are generated by multiple beams of suprathermal ions, while only a single beam is observed at typical IMF strength. The consequences of these differences for solar wind‐magnetosphere coupling are discussed. Plain Language Summary: Our solar system is filled with a stream of particles escaping from the Sun, called the solar wind. The Earth is shielded from these particles by its magnetic field, which creates a magnetic bubble around our planet, the magnetosphere. Because the solar wind flow is supersonic, a bow shock forms in front of the magnetosphere to slow it down. The outermost region of the near‐Earth space is called the foreshock. It is a very turbulent region, filled with particles reflected off the Earth's bow shock, and with a variety of magnetic waves. These waves can be transmitted inside the magnetosphere and create disturbances in the magnetic field on the Earth's surface. In this work, we use supercomputer simulations to study how the foreshock changes when the solar magnetic field, carried by the solar wind, intensifies. This happens in particular during solar storms, which create stormy space weather at Earth and can have adverse consequences on, for example, spacecraft electronics and power grids. We find that the foreshock properties are very different during these events compared to normal conditions and that these changes may have consequences in the regions closer to Earth. Key Points: We study the effects of the interplanetary magnetic field strength on the foreshock properties using hybrid‐Vlasov simulations The foreshock is structured over smaller scales for higher magnetic field strength; waves are less monochromatic and grow in a larger region Suprathermal ion density decreases at higher field strength, and we identify a possible new signature of the foreshock compressional boundary